2019
DOI: 10.3390/toxics7010013
|View full text |Cite
|
Sign up to set email alerts
|

A Model-to-Monitor Evaluation of 2011 National-Scale Air Toxics Assessment (NATA)

Abstract: Environmental research has widely utilized the ambient concentrations of hazardous air pollutants (HAPs) modeled by the National-Scale Air Toxics Assessment (NATA) program; however, limited studies have evaluated the model’s performance. This study aims to evaluate the model-to-monitor agreement of the 2011 NATA data with the monitoring data reported to the U.S. Environmental Protection Agency’s (EPA) Air Quality System (AQS). Concentrations of 27 representative HAPs measured at 274 sites in the U.S. in 2011 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…At various point emission sources, cadmium, lead, and arsenic particulate matter were collected on high-quality filter paper as part of the 2011 National Emissions Inventory. Metals were dissolved in hot acid for extraction and were analyzed using inductively coupled plasma/mass spectrometry [24,25]. The total exposure concentration of cadmium compounds in the air was a county-level metric calculated by the EPA through models using weighted averages of air cadmium concentration levels measured at these various point emission sources.…”
Section: Exposure Datamentioning
confidence: 99%
“…At various point emission sources, cadmium, lead, and arsenic particulate matter were collected on high-quality filter paper as part of the 2011 National Emissions Inventory. Metals were dissolved in hot acid for extraction and were analyzed using inductively coupled plasma/mass spectrometry [24,25]. The total exposure concentration of cadmium compounds in the air was a county-level metric calculated by the EPA through models using weighted averages of air cadmium concentration levels measured at these various point emission sources.…”
Section: Exposure Datamentioning
confidence: 99%
“…Other studies also found discrepancies between NATA estimates and monitored chemical concentrations, due again, in part, to local or indoor sources (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…As for the data quality of NATA or AirToxScreen, independent evaluation of the NATA concentration data has shown good agreement with model to monitor assessments overall, however in the few occasions where there was poor agreement with respect to speci c hazardous air pollutant, the NATA usually underestimated the concentration of the suspected air toxics, meaning the cancer risk in most areas is probably higher 31 . However, if the underestimation is systemic and has no speci c bias towards any given subpopulation, the general conclusions from this study should hold true.…”
Section: Limitationsmentioning
confidence: 99%